2013
DOI: 10.4028/www.scientific.net/amr.838-841.166
|View full text |Cite
|
Sign up to set email alerts
|

Wettability of Alumina Substrates with Micro-Morphology and Microstructure

Abstract: A non-smooth surface with convex domes was fabricated on a chemical polished 2024 aluminum alloy substrate using the method of pressing with a symmetrically distributed concave hole module. Anode oxidation technique was used to prepare alumina films on a non-smooth surface. The as-prepared surfaces possessing microscale morphology and multiscale structures without anything chemical modification exhibited excellent hydrophobicity, and had a maximum water contact angle of about 133o. The microscale morphology of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Buczko et al [11] constructed a superhydrophobic aluminum mechanical surface and found that the greater the current density and the longer oxidation time, the greater the surface roughness of the aluminum substrate and contact angle, and the weaker the wetting performance. Similarly, Li et al [12] prepared alumina film on a non-smooth convex aluminum and discussed the influence of morphology on wettability. The experimental results showed that the water contact angle of the substrate surface could distinctly increase from 80.6 • to 133 • due to the change of the surface morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Buczko et al [11] constructed a superhydrophobic aluminum mechanical surface and found that the greater the current density and the longer oxidation time, the greater the surface roughness of the aluminum substrate and contact angle, and the weaker the wetting performance. Similarly, Li et al [12] prepared alumina film on a non-smooth convex aluminum and discussed the influence of morphology on wettability. The experimental results showed that the water contact angle of the substrate surface could distinctly increase from 80.6 • to 133 • due to the change of the surface morphology.…”
Section: Introductionmentioning
confidence: 99%